Implementation of Differentiated Learning in Identifying Sentence Structures for Fifth Grade Elementary School Students: Analysis of Obstacles and Implementation Solutions - Adnyana, I Ketut Suar; Putu Ronny Angga Mahendra; Wayan Meter; I Gusti Nyoman Putra Kamayana (Universitas Pendidikan Ganesha, 2024)
Differentiated learning in fifth-grade elementary schools in the Untung Surapati cluster, East Denpasar District, has not yet been maximized. Teachers face challenges in implementing differentiated learning when teaching sentence structure. This issue needs to be examined to determine solutions that can be used in sentence structure teaching. The methods used for data collection include observation, interviews, and document analysis. The challenges faced by teachers include: 1) limited teaching staff. To address this, students are divided into several groups. 2) Difficulty understanding the concept of sentence structure. To overcome this difficulty, teachers can use the picture-and-picture method with the assistance of keywords. 3) Limited teaching time. This can be addressed by collaborating with fellow teachers in developing teaching materials. 4) With a large number of students, implementing cooperative learning can be a solution to handling large classes. 5) Teachers' skills in implementing differentiated learning are not yet optimal. Teachers are given opportunities to attend training sessions. 6) Each student has different needs, interests, and skill levels. To address this, teachers create flexible assessment rubrics. 7) Teachers use various teaching approaches to meet the diverse needs of students. Adjusting assessments to different teaching approaches becomes a challenge for teachers. Teachers should create assessment instruments based on the methods applied in teaching.